The moderating effect of gender on premarital sexual practices among the late adolescents in Pahang, Malaysia: an empirical study - Minhat, Halimatus Sakdiah; Raja Ismail, Raja Nurul Najwa; Ying, Lim Poh; Mohd Nazan, Ahmad Iqmer Nashriq (Universiti Putra Malaysia Press, 2024)
Introduction: Premarital sexual is a sexual and reproductive health concern among adolescents in Malaysia. Guided by the constructs of the Social Cognitive Theory (SCT), this study aimed to determine the moderating role of gender on premarital sexual practices among the late adolescents in Kuantan, Pahang. Methods: Probability sampling was utilized to sample the late adolescents from tertiary educational centres. Confirmatory factor analysis (CFA) was conducted to verify the factor structure of the observed variables, with the interrelationship between variables were studied using structural equation modelling (SEM). Moderation analysis was completed via multigroup analysis (MGA). Results: A response rate of 72.2% was obtained, with 390 adolescents aged 18 to 19 years old participated in the study. The total mean for premarital sexual practices was 1.14 ± 0.47, with highest mean observed for masturbation (1.33 ± 0.83). Attitude (β = -0.111, p = 0.021), religiosity (β = -0.014, p = 0.032) and high-risk activities (β = 0.999, p < 0.001) illustrated significant relationships with premarital sexual practices. A moderated regression analysis showed significant interactive effects between gender and premarital sexual practices, with negative association between attitude and religiosity with premarital sexual practices were found among male respondents. Conclusion: This empirical study demonstrated significant moderation effect of gender between attitude and religiosity with premarital sexual practices among targeted late adolescents’ population in Pahang, Malaysia. Any efforts to tackle issue related to premarital sexual practices among similar population should be directed towards male adolescents with lower religiosity score.